Geomorphologische Notizen aus Indonesien - Verstappen, Hermann Theodor (ERDKUNDE, 1955)
The first part of this essay deals with the history of geomorphological research in Indonesia. Research in the proper sense began as late as about 1920 and was mainly carried out by the Cartographical Section of the Topographical Office at Djakarta. Later the scope of this section was extended and its name was changed to Geographical Institute. Before the establishment of this institution many pedologists, zoologists and other scientists had paid attention o the study of landforms, although only as a subsidiary to their respective fields. Since geomorphology is now able to draw from the findings of allied sciences, a rapid further development of this field seems reasonably certain. The second part of the essay outlines the specific tasks which should be undertaken in future research. What is needed first of all is a study of the climatically conditioned landforms, i. e. an investigation into the role played in denudation by the tropical climate. Since denudation proceeds at a rapid rate, there is always a close connexion between youthful landforms and recent tectonic movements. It is in elucidating this connexion that the study of the geomorphology of Indonesia is of greatest importance. Geomorphologists in collaboration with geophysicists should attempt to explain the causes of the dynamism which, in this world of islands, finds its expression in pronounced movements of the earth's crust.